1971
DOI: 10.1136/gut.12.4.268
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of achalasia with pneumatic dilatations

Abstract: SUMMARY During the last 13 years 264 unselected patients with achalasia have been treated solely by the technique of pneumatic dilatation. The principle of the method was to continue the series of consecutive dilatations until the result was satisfactory. This paper reports the late results in 138 patients who were treated more than three years ago (3-13 years; mean 6.6 years). The results were evaluated by somebody who had not before been involved in the treatment of achalasia. The evaluation was based on a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
4

Year Published

1976
1976
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(85 citation statements)
references
References 12 publications
4
77
0
4
Order By: Relevance
“…28 The mean delay in diagnosis is 5 years (range, 2-7 years). [29][30][31][32][33][34][35] Howard et al 36 reported that 36.8% of achalasia patients had been treated for GERD. Additionally, Rosenzweig and Traube 9 showed that the initial diagnosis was achalasia in only 12 of out 25 achalasia patients, whereas the other 13 patients were diagnosed incorrectly.…”
Section: Attributing Factors For Diagnostic Delay In Achalasiamentioning
confidence: 99%
“…28 The mean delay in diagnosis is 5 years (range, 2-7 years). [29][30][31][32][33][34][35] Howard et al 36 reported that 36.8% of achalasia patients had been treated for GERD. Additionally, Rosenzweig and Traube 9 showed that the initial diagnosis was achalasia in only 12 of out 25 achalasia patients, whereas the other 13 patients were diagnosed incorrectly.…”
Section: Attributing Factors For Diagnostic Delay In Achalasiamentioning
confidence: 99%
“…Other complications of pneumatic dilation include development of intramural hematomas, esophageal mucosal tears, and diverticula at the gastric cardia [72] . Severe transient and intermittent postprocedural chest pain has been reported in approximately 15% of patients during the 24-48 h after dilation [73,74] . Although this symptom is disturbing, it is not harmful.…”
Section: Pneumatic Dilationmentioning
confidence: 99%
“…Predictors of the best clinical outcomes after PD include: age older than 40 years, women, LES pressure after dilatation <10 mmHg and type II pattern by HRM (14,23,45,46).…”
Section: Pneumatic Dilationmentioning
confidence: 99%